Communication Violence in Verbal Expression and Nonverbal Behavior of Preschool and Early Primary School Teachers During Teaching Process: An Observational Study - Stamatis, Panagiotis J. (International Journal of Criminology and Sociology, 2017)
The teaching process is actually a communication one. It could be interesting or not, pleasant or woeful etc. depending mainly on the teacher’s attitude, his/her verbal expression and nonverbal behavior performed in the classroom. Especially, in children of preschool and early primary school ages, the words a teacher uses in an everyday chat or discussion with students during teaching, the tone of his/her voice and nonverbal behavior may create a positive or negative classroom climate which affects relationships among him/her and the students. This study, based on observations of teachers’ communication behavior during teaching process, focuses on the way they choose to communicate with children and on their verbal expressions in regard to classroom climate conditions. Also, the study focuses on teachers’ nonverbal behaviors, which like nonverbal communication aspects, affect the relationships among classroom participants in school environment. Emphasis is given on teachers’ verbal expressions and nonverbal behaviors that may lead to communication violence and bullying because teachers are more than often behavioral patterns especially for preschoolers and very young elementary school children (pupils).